Creative Cuisine in The Mountains: Yörük Food Culture - Akdag Gürkan; Soylu Aykut Göktuğ (BIO Web of Conferences)
Rooted in the nomadic lifestyle of the Yörük people, the Yörük food culture reflects a unique combination of simplicity, practicality and rich flavours. The Yörüks, a Turkish ethnic group traditionally living in the mountainous regions of Southern and Western Anatolia in Turkey, have a distinctive culinary heritage shaped by their nomadic nature and pastoral economy. In this context, the aim of this study is to introduce the culinary culture of the Yörüks and provide information on the eating and drinking habits of the Yörüks. In this way, it will be possible to preserve, support and promote the centuries-old traditional food heritage of the Yörük culture in the field of tourism. In accordance with the aim of the study, visits were made to regions where the Yörüks live compactly within the province of Mersin, field observations and semi-structured interviews were conducted with 25 Yörük representatives. In this way, information was collected on the foods frequently consumed by the Yörüks. In addition, information about the food culture of the Yörük people was provided. According to the results, it can be said that the food practices of the Yörük people are formed around livestock, especially goats and sheep, from which they obtain basic ingredients such as milk, butter, yogurt, and cheese. These dairy products are usually processed into shelf-stable products such as dry yogurt and tulum cheese, which are suitable for a nomadic lifestyle and form the basis of their diet. Meat, especially lamb and goat, is another main component of Yörük cuisine. Meat is prepared in simple yet delicious ways, usually grilled or boiled. Cooking dried meat and eating natural herbs collected from the highlands are common. In the Yörük food culture, grains such as bulgur and wheat are used to prepare staple dishes such as flatbreads and tortillas. These dishes are usually cooked over an open fire and are seen as a reflection of the active and productive lifestyle of the Yörük people. Seasonal gathering of wild herbs, fruits and nuts also plays an important role in the Yörük diet. In conclusion, the Yörük food culture remains a testament to the resourcefulness and adaptability of a people who have managed to survive in harsh climates for centuries.